The Relationship of Information Sources with Adolescent Behavior about Personal Hygiene During Menstruation - Evi Yuniarti; Ayu Nina Mirania; Stephanie Lexy Lexy Louis (Indonesian Journal of Global Health Research, 2025)
Adolescent girls are a group that is very vulnerable to infections in the reproductive organs due to lack of knowledge and poor behavior in maintaining personal hygiene during menstruation. Information about the cleanliness of the genitals during menstruation is very important for adolescent girls to know, information can be obtained through parents, peers and teachers at school is very important for building good reproductive health. The purpose of this study is to find out the relationship between information sources and adolescent behavior about personal hygiene (genetalia) during menstruation. The type of research conducted is a quantitative analytical survey method with a cross sectional approach. This research will be conducted in July-September 2022 with a population of all students in class XI Science at MAN I Palembang with sampling using purposive sampling techniques. The data collection technique using questionnaires and data was analyzed using the Chi Square statistical test. Based on the results of the analysis, it was shown that out of 35 people, 56.4% had positive personal hygiene behavior, while from 57 people who received indirect information, 89.2% had negative personal hygiene behavior. The results of the Chi Square analysis test obtained a p value = 0.000 (< 0.05) showing that there was a significant relationship between information sources and adolescent girls' behavior about personal hygiene (genetalia) during menstruation. Based on the results of this study, it is suggested that schools can create innovative programs as an effort that can be made for adolescent reproductive health.